2009
DOI: 10.1111/j.1083-6101.2009.01455.x
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Ensuring Participant Consent in Internet-based Sex Studies: A Case Study of the Men's INTernet Sex (MINTS-I and II) Studies

Abstract: This study documents our experience in designing, testing, and refining human subjects’ consent protocol in 3 of the first NIH-funded online studies of HIV/STI sexual risk behavior in the USA. We considered 4 challenges primary: a) designing recruitment and enrollment procedures to ensure adequate attention to subject considerations; b) obtaining and documenting subjects’ consent; c) establishing investigator credibility through investigator-participant interactions; d) enhancing confidentiality during all asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In one experimental study, Varnhagen and colleagues (2005) found that participants recalled more information from consent forms in brief formats as opposed to longer ones. Perhaps bulleted key information (e.g., “chunking,” Simon Rosser et al, 2009) can aid in recall and recognition of important information about the study prior to participation. While the Internet appears to be a comparable medium to traditional paper-and-pencil questionnaires for obtaining personality measures (Buchanan & Smith, 1999), we found differences via presentation medium, such that those reading paper consent forms in-person appeared to recall greater details within the form compared to those reading the consent form online (as evidenced of remembering the embedded term lucky charms).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one experimental study, Varnhagen and colleagues (2005) found that participants recalled more information from consent forms in brief formats as opposed to longer ones. Perhaps bulleted key information (e.g., “chunking,” Simon Rosser et al, 2009) can aid in recall and recognition of important information about the study prior to participation. While the Internet appears to be a comparable medium to traditional paper-and-pencil questionnaires for obtaining personality measures (Buchanan & Smith, 1999), we found differences via presentation medium, such that those reading paper consent forms in-person appeared to recall greater details within the form compared to those reading the consent form online (as evidenced of remembering the embedded term lucky charms).…”
Section: Discussionmentioning
confidence: 99%
“…Benefits of online research are numerous and include ease and expanded time of access, reduced cost and paperwork burden, ability to recruit a large and representative sample through email and survey link invitation, and perhaps more accurate data due to greater anonymity for stigmatizing attitudes and behaviors (Gosling, Vazire, Srivastava & John, 2004; Simon Rosser et al, 2009; Stretcher, 2007). As more research is conducted over the Internet, the importance of examining attention to details in online statements outside of the laboratory is apparent (Kraut et al, 2004).…”
Section: Online Consentmentioning
confidence: 99%
“…Eligible participants should be directed to the online consent form and then to the data collection instrument. For information about how to obtain consent online, please see Rosser et al (2009).…”
Section: Preparing For Online Data Collectionmentioning
confidence: 99%
“…Internet users may also be more acclimated to list-based or brief summaries when they do choose to consume textual information. Previous Web-based research with MSM has also shown that brief consent summaries may improve consent information comprehension over a standard consent process, but this research was done before Web-based interactions became more photo- or video-focused and therefore we did not examine this alternative [19,25]. The objective of our study was to assess if comprehension of key informed consent facts improved through the use of these new techniques versus a standard text-based informed consent form.…”
Section: Introductionmentioning
confidence: 99%